PENGARUH PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP PRESTASI BELAJAR SISWA SMAN 2 KALIANDA - Dio Renaldi; Very Hendra Saputra (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2021)
Education is one of the most important things in social life, because education is one of the people's mindsets to survive. The next generation of the nation must have education in order to compete nationally and internationally Puspaningtyas (2019). The results of the 2018 Program for International Student Assessment (PISA) study which compared the math, reading and science performance of each child in 79 countries. For the math category, Indonesia was ranked 73, for reading ability Indonesia was ranked 74, in the science performance category. , Indonesia is ranked 71st. Based on the results of the report, Indonesia's performance appears to be declining when compared to the 2015 Tohir PISA report (2019). Based on this, the decrease in lift is influenced by several factors, one of which is internal factors, one of which is the difficulty of students in understanding the material it can affect student achievement. student learning, but this can be overcome with the PMR approach model, based on the results of the study showing that PMR has an effect on learning achievement based on the results of the two-average difference test which is below or less than 0.05 which means that it can be concluded that the  Realistic Mathematics education Approach affect student achievement.Keywords: PMR and Learning achivement